The effect of blended task-oriented flipped classroom on the core competencies of undergraduate nursing students: a quasi-experimental study - Li Ke; Lanlan Xu; Li Sun; Juan Xiao; Lingxuan Tao; Yixue Luo; Qiongya Cao; Yan Li (BMC Nursing, 2023)
Abstract Background The flipped classroom (FC) method is becoming increasingly popular in China's nursing education. It is an important breakthrough improvement in the quality of learning in nursing education reforms. Purpose This study aimed to determine the effects of blended task-oriented flipped classroom (TFC) on nursing students undertaking the Fundamentals of Nursing course. Methods A pre-and post-test quasi-experimental design was adopted. This study was conducted in the Autumn semester, 2021 academic year in a Chinese university. Using cluster sampling technique, this study enrolled second-year undergraduate nursing students from six classess who were studying Fundamentals of Nursing course. A blended TFC was developed and implemented with three classes (experimental group: n = 152). In-class traditional lectures were applied to the other three classes (control group: n = 151). The Self-Directed Learning Instrument, Problem-Solving Inventory, and California Critical Thinking Disposition Inventory were used to evaluate students’ learning outcomes, and final examinations were conducted at the end of after course. In addition, students in the flipped classroom group were required to answer five open-ended questions concerning their flipped classroom learning experiences. Results Students in the experimental group showed significant improvement in academic performance compared to those in the control group (p = 0.001). Considering total scale and factors, students in the experimental grouped recorded significantly higher scores in self-directed learning ability, problem-solving skills, and critical thinking ability compared to those in the control group (p < 0.05). Furthermore, improved abilities and skills such as team cooperation, communication, presentation, identifying /solving clinical problems, and accountability were reported. Conclusion A blended TFC teaching approach positively impacted students' core competencies and improved learning outcomes in the Fundamentals of Nursing course.